2022
DOI: 10.3389/fpsyg.2022.885619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intrinsic and Extrinsic Gaming Elements on Online Purchase Intention

Abstract: Gamification is a developing trend that can work on customers' motivation and performance in online business areas. Notwithstanding, it is still vigorously debated as there is a continuous conversation inside the gamification community about whether individual gamification elements may really weaken or improve on customers' intrinsic and extrinsic motivations as well as the effect on the consumer's perceived enjoyment and purchase intention. The study uses a questionnaire survey as the research method. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Perceived enjoyment, characterized by joy, delight, and pleasure ( Akdim et al, 2022 ), is a primary motivator for media usage and technology adoption ( Ma, 2021 ). Previous studies have demonstrated the positive impact of perceived enjoyment on consumer behavioral intentions ( Wang et al, 2013 ; Wu and Santana, 2022 ). For instance, perceived enjoyment has been shown to positively correlate with engaging in social commerce on shopping websites ( Zheng et al, 2020 ).…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…Perceived enjoyment, characterized by joy, delight, and pleasure ( Akdim et al, 2022 ), is a primary motivator for media usage and technology adoption ( Ma, 2021 ). Previous studies have demonstrated the positive impact of perceived enjoyment on consumer behavioral intentions ( Wang et al, 2013 ; Wu and Santana, 2022 ). For instance, perceived enjoyment has been shown to positively correlate with engaging in social commerce on shopping websites ( Zheng et al, 2020 ).…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…Following these literatures, gamification in our research contexts refers to the incorporation of game design elements into the fitness apps while retaining its instrumental functions for promoting or supporting users’ physical activity/exercise. As an emerging design approach, gamification has attracted a large stream of researches in various contexts, including fitness/health/exercise ( Cheng, 2020 ; Whelan and Clohessy, 2020 ; Yang and Li, 2021 ; Li et al, 2023 ), education ( Sánchez Prieto et al, 2021 ; Behl et al, 2022 ; Chen and Liang, 2022 ; Ghai and Tandon, 2023 ; Oliveira et al, 2023 ; Zhang and Hasim, 2023 ), marketing ( Zhang et al, 2021 ; Wu and Santana, 2022 ), sustainable consumption ( Mulcahy et al, 2020 ), online community ( Xi and Hamari, 2019 ).…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%
“…In the article by Wu and Santana (2022), the records present the study by Kaynak and Basal (2019) that found that "extrinsic elements of gambling positively influence perceived pleasure." To corroborate the idea, previous studies have recommended that customers get a higher level of enjoyment from accumulating points and badges (Codish and Ravid, 2017).…”
Section: Extrinsic Motivation Strategiesmentioning
confidence: 99%